„Revolution, cinema, painting: creative recycling of images in the films of Tom Gotovac (Antonio Lauer)“ - Gilić, Nikica (Array, 2010)
Tomislav/Tom Gotovac (Antonio Lauer), one of the leading Croatian conceptual and multimedia artists, successfully recycles visual images in his recent films, as demonstrated in the best works of his more recent opus. By using stills and inserts from his own films and from films important for him or his art (e.g. films by George Stevens, Lazar Stojanovic’, the Vasiliev brothers), but also from famous paintings (by Diego Rivera, Frida Kahlo) and popular songs, Gotovac’s films (Tomislav Gotovac, Dead Man Walking, Proroci) transcend the borders of cinema as much as his performances and exhibitions transcend borders of every medium of artistic creation. However, certain general questions are raised by such artistic procedure: broadly speaking, today’s conceptual art is institutionalized in some sort of artistic ‘genre’ and Gotovac/Lauer seems to be a true master of that genre.